Excretions of Urinary Creatinine on Young and Mature Kacang Goat under Different Feeding Levels - Mukminah, Nurul; Rianto, Edy; Purbowati, Endang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
Abstract. This study was aimed to examine the excretion of urinary creatinine in young and mature Kacang goat bucks under different feeding levels. This study used 16 Kacang goat bucks consisting of 2 groups of age, i.e. eight young bucks (aged 6-7 months, weighed 12.75Â±2.68 kg) and 8 mature bucks (age 9-12 months, weighed 17.34Â±3.32 kg). The bucks were fed pelleted complete feed containing 78.82% dry matter (DM), 18.80% crude protein (CP), and 76.29% total digestible nutrients (TDN). The bucks were allocated into a 2x2 nested design with four replications. The treatment was the amount ofÂ 2.24% dry matter intakeÂ (T1) and 4.48% of body weight (BW) (T2) for the young goat, while the mature buck was 1.87% and 3.74%, respectively. The results showed that DM, CP and TDN intake were significant different across ages and highly significantly different between feeding levels. Changes of urinary creatinine from week 0â12 showed no differences in the age group (142 mg/dl) and feeding level (143 mg/dl). Conclusively, age and feed level affected body weight, feed intake and creatinine excretion of Kacang Goat.Â The more body weight gain (age) and feed level, the more urinal creatinine excretion in male Kacang goat.Â Key words: Kacang goat, ages, feeding level, and creatinineÂ Abstrak. Penelitian ini bertujuan untuk mengkaji kadar kreatinin pada kambing Kacang muda dan dewasa dengan jumlah pemberian pakan yang berbeda. Materi berupa 16 ekor kambing Kacang jantan, terdiri dari 8 ekor umur muda (6-7 bulan) dan 8 ekor umur dewasa (9-12 bulan). Pakan komplit yang diberikan memiliki kandungan bahan kering (BK) 78,82%, protein kasar (PK) 18,80%, dan total digestible nutrients (TDN) 76,29%. Rancangan penelitian ini adalah pola tersarang 2x2 dengan 4 ulangan. Perlakuan pakan berupa jumlah BK pakan yang diberikan yaitu 2,24% bobot badan (BB) (T1) dan 4,48% BB (T2) untuk kambing muda, sedangkan kambing dewasa sebesar 1,87% BB (T1) dan 3,74% BB (T2). Hasil penelitian menunjukkan bahwa konsumsi BK, PK dan TDN berbeda nyata pada kelompok umur dan berbeda sangat nyata pada perlakuan pakan. Kadar kreatinin pada minggu ke 0-6 tidak berbeda nyata, namun pada minggu ke 12 berbeda nyata baik kelompok umur maupun akibat perlakuan pakan. Perubahan kadar kreatinin dari minggu ke 0-12 menunjukkan perbedaan yang tidak nyata pada kelompok umur dan perlakuan pakan. Kesimpulan dari penelitian ini adalah kadar kreatinin semakin meningkat dengan semakin meningkatnya bobot badan (umur) dan pakan ternak.Â Kata kunci : kambing Kacang, umur, level pakan, dan kreatinin